Creating climate-smart multi-functional landscapes through integrated soil, land and water management practices and contextualized agroadvisory services at different scales in Ethiopia - Tamene, Lulseged D.; Abera, Wuletawu (Bioversity International and the International Center for Tropical Agriculture, 2020)
Experiences show that integrating restoration efforts at landscape level need to be coupled with intensification efforts at farm/plot level to promote synergy and attain multiple benefits. The approaches followed in the creation of multifunctional landscapes are designed to enable achieving this goal. This report presents project activities and outputs related to approaches, implementation modalities and evidence generation exercises from ‘learning’ and upscaling sites. The approaches followed in terms of partnerships and stakeholder engagement are briefly described as these are critical for successful project implementation. Climate-smart agriculture (CSA) and agricultural intensification practices were implemented at landscape and farm level scales. Both farm level interventions related to fertilizer response and irrigation optimizations practices and landscape interventions related to CSA and sustainable land management (SLM) options were implemented at climate-smart villages (CSVs) and scaling sites. Evidence generation related to the impacts of the different practices from project sites and other successful cases in the country was also key component of the activities. These were instrumental to target and scaling technologies. Finally, effort towards integrated conceptual approaches and practical tools to facilitate the targeting and scaling of practices as well as near real-time evidence generation are presented.